The prevalence and risk factors for diabetes mellitus in healthcare workers at Tygerberg hospital, Cape Town, South Africa: a retrospective study. Issue 3 (2nd September 2019) - Coetzee, Ankia; Beukes, Amanda; Dreyer, Reinhardt; Solomon, Salaamah; van Wyk, Lourentia; Mistry, Roshni; Conradie, Magda; van de Vyver, Mari
Abstract : Objectives: To assess the contribution of traditional and modifiable risk factors to the overall risk and prevalence of type 2 diabetes mellitus (T2DM) amongst health workers (HWs) in the public sector. Design: A retrospective analysis was performed on data obtained from 260 participants. Setting and subjects: HWs at Tygerberg Hospital, Western Cape attending the World Diabetes Day (WDD) metabolic screening and educational event. Outcome measures: The 10-year risk stratification for T2DM was calculated in all HWs attending the WDD event. This was based on the Finnish 'Test2prevent' diabetes risk calculator endorsed by the International Diabetes Federation assessing a set of well-established metabolic risk factors. Self-reported consumption of sugar-sweetened beverages (SSBs) was added to the questionnaire but did not add to the risk calculation. Results: The prevalence of known hyperglycaemia in this cohort is concerning (11%, n  = 62). An additional 29 health workers were identified as at high risk to develop T2DM within 10 years. Consumption of SSBs and minimal physical activity were identified as modifiable targets for intervention. Conclusions: Education and lifestyle interventions are of paramount importance to ensure the metabolic health of HWs and their communities. Policies and guidelines focused on limiting unhealthy/obesogenic work environments are urgently needed.